Transformation of the musical education derivate from the COVID-19 pandemic: From traditional teaching to the use of virtual environments - Velazco-Reyes, Benjamin; Palacios-Serna, Lina Iris; Estrada-Araoz, Edwin Gustavo; Velez-Jimenez, Dolores; Cortez-Chavez, Claudia Virginia (International Journal of Innovative Research and Scientific Studies, 2025)
As a result of the COVID-19 pandemic, music universities in Peru have had to adapt to new ways of providing educational services. Consequently, teachers have transformed their practices to achieve virtual teaching by applying various technological resources. This research aims to analyze how music teachers transformed traditional teaching-learning processes to fit the new virtual environments derived from the restrictions due to COVID-19. The analysis is conducted within a qualitative approach using the phenomenological method, and the data collection involved twenty-one interviews with teachers from four public universities in Peru. The results indicate that teachers of theoretical courses easily adapted to the virtual environment, while those teaching practical courses faced challenges that could not be overcome. Regarding modifications to the methodology, there are divergent opinions; an important resource was home videos, as they can enhance student performance and enable objective evaluation by the teacher. Additionally, digital competence must be integrated into the study curricula for a comprehensive education of the student.